WASTE GENERATION DURING THE PRODUCTION ACTIVITIES OF THE KARAGANDA METALLURGICAL PLANT AND ENVIRONMENTAL PROTECTION MEASURES - Azimova Asaloy Shavkatjon qizi (Modern American Journals, 2025)
The Karaganda Metallurgical Plant is located in Temirtau, Karaganda region, located in the central part of Kazakhstan. The region is a highly elevated territory with absolute elevations of 400-1000 m, geomorphologically quite heterogeneous. The relief is characterized by the presence of shallow depressions, dry watercourse beds, river valleys, hollows with groundwater outlet, drainless depressions, steppe saucers and lake basins.